Fraksinasi Ekstrak Butanolik Kaldu Fermentasi Isolat Kapang Tanah Banjarmasin Biomcc-F.T.3762 Berbasis Uji Aktivitas Penghambatan Dihidroorotat Dehidrogenase Plasmodium falciparum - AMILA PRAMISANDI; HARMITA HARMITA; ANIS HERLIYATI MAHSUNAH (Fakultas Farmasi Universitas Pancasila, 2017)
Butanolic extract of soil fungus BioMCC-F.T.3762 fermentation broth exhibited inhibitory activity against Plasmodium falciparum dihydroorotate dehydrogenase (PfDHODH), a fl avin dependent mitochondrial electron transport chain, an essential enzyme in de novo pyrimidine biosynthesis pathway of the parasite. The crude butanolic extract exhibited PfDHODH inhibition of 97% at a concentration of 413 μg/mL, and showed no inhibitory activity against its human homolog. Bioassayguided fractionation was performed on butanolic extract of microbial fermentation broth to isolate the active compounds. The active fraction was isolated using liquid–liquid partition, silica gel column chromatography, octadecylsilane (ODS) column chromatography and was purifi ed by preparative high performance liquid chromatography (HPLC). Major peak of active fractions, FS10-2-12 and FS10-2- 13, were detected by PDA HPLC, which showed a retention time of 12.6 minute and 13.9 minute at 254 nm, respectively. The active fractions exhibited 75% and 40% inhibitory activity against PfDHODH, respectively, at a concentration of 100 μg/mL. In comparison, atpenin A5, a known potent mitochondrial complex II inhibitor exhibited 75% inhibitory activity againts PfDHODH at 366 μg/mL.